An Overview of Dynamic Descriptions for Nanoscale Materials in Particulate Photocatalytic Systems from Spatiotemporal Perspectives - Jiawei Yan; Zhidong Wei; Kai Takagi; Masaya Motodate; Zhi Jiang; Chiaki Terashima; Wenfeng Shangguan (Nano-Micro Letters)
Highlights The dynamic descriptions for nanoscale particulate photocatalysts have been elucidated in terms of the irradiation field, photo-excited carrier behavior and interfacial reaction in the photocatalytic systems. The advanced spatiotemporal characterization techniques and evaluation methods are collected with the introduction of recent works and applications. The challenges and prospects in the elaborate investigation of photocatalytic dynamics are discussed.